Knowledge and Perception of Premarital Screening within Young Adults : Study at STIKES Bhakti Husada Mulia - Dewi, Kunawati Tungga; MS, Novi Paramitasari; Afindaningrum, Rochmanita Sandya (Universitas Pahlawan Tuanku Tambusai, 2024)
Premarital screening (PMS) is a screening procedure offered to couples planning to marry to check for genetic and infectious disorders in order to reduce the risk of disease transmission to their offspring. This preventative intervention will help to reduce the incidence of specific genetic illnesses related with marriage. The primary objective of this study was to describe young adults’ knowledge and perceptions about premarital screening in a university setting. Method This study used a cross-sectional design with an online survey method. The respondents to this study were midwifery students at STIKES Bhakti Husada Mulia. Chi-square was utilized in the data analysis. The study found a significant association between knowledge level and age group (p < 0.018). 37% of respondents learned about PMS through formal education, 33% from social media, 24% from health services, and the others from television and friends. Statistical study with chi-square revealed a significant association between perception level and age (p = 0.045). Conclusions from the research indicate that the majority of midwifery students have good knowledge and perception of PMS.